2020
DOI: 10.1007/jhep11(2020)081
|View full text |Cite
|
Sign up to set email alerts
|

QED factorization of non-leptonic B decays

Abstract: We show that the QCD factorization approach for B-meson decays to charmless hadronic two-body final states can be extended to include electromagnetic corrections. The presence of electrically charged final-state particles complicates the framework. Nevertheless, the factorization formula takes the same form as in QCD alone, with appropriate generalizations of the definitions of light-cone distribution amplitudes and form factors to include QED effects. More precisely, we factorize QED effects above the strong … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
98
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(101 citation statements)
references
References 51 publications
(151 reference statements)
3
98
0
Order By: Relevance
“…An example of which is provided by B s → µ + µ − , where it was found that the chirality suppression of the non radiative decay m µ /m b is lifted to m µ /Λ QCD ("enhanced power corrections") when QED corrections are taken into account [33]. These authors develop QED corrections to B decays within the soft collinear effective theory (SCET) framework, recently extended to B → Kπ [34]. It allows for the resummation of different types of logarithms [35] Another approach is lattice QCD, where the precision in Kaon physics per se demands the inclusion of QED corrections [36,37] with first results in leptonic decays [38][39][40].…”
Section: Jhep12(2020)104mentioning
confidence: 99%
“…An example of which is provided by B s → µ + µ − , where it was found that the chirality suppression of the non radiative decay m µ /m b is lifted to m µ /Λ QCD ("enhanced power corrections") when QED corrections are taken into account [33]. These authors develop QED corrections to B decays within the soft collinear effective theory (SCET) framework, recently extended to B → Kπ [34]. It allows for the resummation of different types of logarithms [35] Another approach is lattice QCD, where the precision in Kaon physics per se demands the inclusion of QED corrections [36,37] with first results in leptonic decays [38][39][40].…”
Section: Jhep12(2020)104mentioning
confidence: 99%
“…The study of QED effects in B-meson decays has become an active field of research in recent years [1][2][3][4][5][6][7], as such effects will become increasingly more important when higher experimental precision is reached. The standard treatment of QED effects assumes the mesons to be point-like to very small distances of order 1/m B .…”
Section: Introductionmentioning
confidence: 99%
“…This allows for a clear separation of very lowenergetic photons with a point-like coupling to mesons from photons with energy of order Λ QCD up to m B , at which scale one can use the 1/m B expansion. First studies following this path were made in [1][2][3][4]. In particular, in [3] we have shown that the QCD factorization formula [8,9] for non-leptonic charmless B decays into two light mesons, B → M 1 M 2 , can be extended to include QED corrections to all orders in α em .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This refactorization is similar in spirit to that performed in section 4.2 of refs [42,43],. albeit in a different physical context.…”
mentioning
confidence: 84%